INDUSTRIALISASI PERIKANAN DALAM PENGEMBANGAN WILAYAH DI JAWA TIMUR - Hakim Miftakhul Huda; Yeti Lis Purnamadewi; Muhammad Firdaus (TATALOKA, 2015)
Disparity of development, poverty and unemployment is one of the main problems of East Java Province. On the other hand East Java province has great potential fishery. This study aims to analyze the role of the fisheries sub-sector in the regional economy of East Java province, knowing the factors that influence the fisheries development and arrange  the fisheries development strategy in  East Java province. Processing data using descriptive analysis, input-output (IO) and multiple linear regression. Fish processing subsector provide the largest multipliers of employment, output and value added among fisheries subsector. Inland fisheries subsector provide the largest of total linkages between fishery subsector, whereas the marine fisheries subsector have the largest of output value among the fishery subsector. Labor and maritime affairs and fisheries budget have a positive influence on the development of fisheries. Fisheries development strategy should be carried out simultaneously between marine, inland and fisheries processing. Fisheries industrialization strategy is expected to increase the value added of fisheries and reduce the disparity of development, poverty and unemployment.